PENGARUH MUSIM TERHADAP KERAGAMAN DAN KELIMPAHAN KOPEPODA (KRUSTASEA) DI PERAIRAN MANGROVE ESTUARI T. N. UJUNG KULON, BANTEN - Mulyadi; Conni M. Sidabalok (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
An observation on Copepoda diversity and abundance in three mangrove estuaries in Ujung Kulon National Park, Banten was carried out in June and November 2008. The objective of this observation was to investigate the relationship between diversity and abundance of copepods with some environmental factors which affected the distribution in dry and rainy seasons. A total of 28 species from 17 genera and 14 families of copepods were recorded. The highest density of the copepod community was recorded in June (dry season) while the lowest density was in November (rainy season). The diversity, abundance and distribution of copepods were found to be different in the three sites.